Apuntes sobre las relaciones entre el pensamiento, la lengua y la cultura, en el caso andino - Souffez, Marie-France (1984)
This article reproduces some general ideas about the problems of the Peruvian educational system vis-à-vis the Andean culture. It advances some research proposals and develops a theoretical position that underlines, alongside the different studies on man in its generality and permanence, the importance of exploring the variations of the human spirit in different cultures and times, which could be useful in Peru, a multicultural country dominated by one culture. Likewise, it proposes to investigate, within the Andean specificity, the ways of thinking and expressing intelligence valued in this culture, beginning the approach by an analysis of the meanings of linguistic expressions related to these forms.